Modification of coconut shell charcoal for metal removal from aqueous solutions - Zahra, Samreen; Mahmood, Zahid; Deeba, Farah; Sheikh, Asma; Bukhari, Hamim; Mehtab, Habiba (European Journal of Chemistry, 2022)
Treatment of the contaminated aqueous solutions to improve their quality is indispensible for their reuse resulting in an emergent challenge to develop facile, nontoxic and less energy consuming techniques to purify water. Present study is therefore aimed at the synthesis of an adsorbent using agricultural waste i.e. coconut shell. The charcoal obtained from coconut shell was modified by acid activation and manganese doping following a simple chemical route. The products were characterized by scanning electron microscopy, energy dispersive X-ray analysis and infrared spectroscopy. Preliminary studies were carried out to compare the adsorption potential of acid modified coconut shell charcoal (AMCSC) and manganese doped coconut shell charcoal (MDCSC) for the removal of chromium (VI) and iron (III) from aqueous solutions. Various physicochemical parameters such as adsorbent dosage, initial metal ions concentration and pH were studied. MDCSC was found to be a better adsorbent for metals as compared to AMCSC and removed chromium more efficiently than iron from synthetic solutions i.e. 56.10% at optimum conditions i.e. 0.6 g/L adsorbent dosage, 10 mg/L initial metal ions concentration and pH = 3. The effect of adsorbents on color and conductivity of the aqueous solutions was also noted; slight variation in color of all the aqueous solutions with a maximum of 91.67% removal was observed.